2015
DOI: 10.1016/j.mjafi.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak control of community acquired pneumonia in a large military training institution

Abstract: The study highlights the importance of Streptococcus pneumoniae as a causative organism for outbreaks of community acquired pneumonia (CAP) in large residential training institutions and reiterates the need for formulating a policy for continuous surveillance. It also highlights the importance of the novel method of using chemoprophylaxis for control of an ongoing outbreak of CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1 Refers to infections that spread through sustained close contact rather than through casual contact (i.e., cold/flu microbes) 2 Reported incidence is likely not the true incidence as many authors included only patient participants or did not include data for participants lost to follow-up 3 Methods of confirmation of disease include: (a) isolation of pathogen from normally sterile site, (b) using a plaque reduction neutralization test, (c) using a real-time reverse transcription polymerase chain reaction, (d) serologically positive for infection as per specific antibody testing 4 Refers to symptoms of disease without microbiological testing on the transfer of participants during the study resulting in further spread to other locations [18,[24][25][26], and on personnel lost to follow-up [27][28][29], so true disease incidence could not be determined. Moreover, a few studies reported on the presence of travelling military personnel in civilian areas (e.g., airports; public transit) [30,31], providing opportunities for transmission between military and civilian populations.…”
Section: Disease Transmission Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Refers to infections that spread through sustained close contact rather than through casual contact (i.e., cold/flu microbes) 2 Reported incidence is likely not the true incidence as many authors included only patient participants or did not include data for participants lost to follow-up 3 Methods of confirmation of disease include: (a) isolation of pathogen from normally sterile site, (b) using a plaque reduction neutralization test, (c) using a real-time reverse transcription polymerase chain reaction, (d) serologically positive for infection as per specific antibody testing 4 Refers to symptoms of disease without microbiological testing on the transfer of participants during the study resulting in further spread to other locations [18,[24][25][26], and on personnel lost to follow-up [27][28][29], so true disease incidence could not be determined. Moreover, a few studies reported on the presence of travelling military personnel in civilian areas (e.g., airports; public transit) [30,31], providing opportunities for transmission between military and civilian populations.…”
Section: Disease Transmission Populationsmentioning
confidence: 99%
“…This mechanism is only applicable to the subset of articles taking place in training facilities (24%; 51/210), of which a majority (84%; 43/51) reported on it. Training assignments in remote and/or unmaintained areas (e.g., marshes) and participation in exercises with heavy physical components [25] were significantly associated with disease transmission. Specifically, travel to endemic areas, nocturnal exercises, low crawl training, sleeping in tents, poor nutrition and/ or dehydration, and crowded training bases were identified among possible risk factors for infection [53,54].…”
Section: Institutionalmentioning
confidence: 99%
“…Specifically, studies reported on military personnel assigned to complete multinational exercises, [17][18][19] with leave granted upon exercise completion 14,20 and subsequent travel of suspected cases to other locations, likely spreading disease. Studies also reported on the arrival of returning infected soldiers and infected recruits leading to outbreaks in the study population, or on the transfer of participants during the study resulting in further spread to other locations, 15,[21][22][23] and on personnel lost to follow-up, 24-26 so true disease incidence could not be determined. Moreover, a few studies reported on the presence of travelling military personnel in civilian areas (e.g., airports; public transit), 27,28 providing opportunities for military-to-civilian or civilian-to-military transmission.…”
Section: Policymentioning
confidence: 99%
“…42 Similarly, another article found that prophylaxis non-compliance was significantly correlated with disease, 47 with numerous others identifying prophylaxis non-compliance as a probable factor. 22 Other behavioural factors likely correlated with infection included lack of use of mosquito nets and approved-grade insect repellent sprays, and failure to wear permethrin-dipped and skin-covering clothing. 15 High-risk behaviour.…”
Section: Individualmentioning
confidence: 99%
See 1 more Smart Citation